Design and Build an Internship Information System at PT. Perkebunan Nusantara IV Regional I Medan Web Based - Herman, Mutia; Muhammad Richie Hadiansah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The administrative process for the internship program at PT Perkebunan Nusantara IV Regional I Medan is still carried out conventionally, starting from the registration stage to recording attendance and daily journals. This situation causes various problems such as input errors, delays in the verification process, and difficulties in monitoring the attendance and activities of interns. This study aims to design a web-based internship information system as a solution to improve data management efficiency and reduce existing administrative problems. The method used in this study follows the SDLC approach with the Waterfall model, which includes needs analysis, system design, implementation with Laravel and Tailwind CSS, and testing using the Black Box Testing method. The findings of this study indicate that the developed system can support online registration, location-based attendance, daily journal filling, and participant management by the admin more quickly, accurately, and integrated. Testing shows that all main functions operate according to the specified scenario. This system makes a significant contribution to supporting more efficient and up-to-date internship administration and has the potential for further development to improve the quality of internship services at related institutions.